2018
DOI: 10.1373/clinchem.2017.272369
|View full text |Cite
|
Sign up to set email alerts
|

Wearables for Promoting Physical Activity

Abstract: There are many research studies documenting the validity and intervention effectiveness of consumer-WPAMs; evidence is emerging on the health benefits linked to use of such devices. Future work on the long-term effects of consumer-WPAMs on behavior and health is warranted, and prospects appear exciting as wearable technology advances and adoption increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 24 publications
0
41
0
2
Order By: Relevance
“…Given the role played by physical activity in determining health outcomes, there has been great interest in the use of wearables in healthcare. Most research on wearables thus far has been focused on their utility in promoting increased physical activity in healthy and diseased populations [ 8 ]. Whereas most studies reported increased physical activity after wearable introduction [ 8 ], there is little evidence that this intervention results in clinically significant health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the role played by physical activity in determining health outcomes, there has been great interest in the use of wearables in healthcare. Most research on wearables thus far has been focused on their utility in promoting increased physical activity in healthy and diseased populations [ 8 ]. Whereas most studies reported increased physical activity after wearable introduction [ 8 ], there is little evidence that this intervention results in clinically significant health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on wearables thus far has been focused on their utility in promoting increased physical activity in healthy and diseased populations [ 8 ]. Whereas most studies reported increased physical activity after wearable introduction [ 8 ], there is little evidence that this intervention results in clinically significant health outcomes. For instance, a year-long study conducted on corporate employees showed that although wearable introduction increased moderate to vigorous physical activity, it did not improve health outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transistors with wide and narrow gates both on the glass and PEN are shown. For transistors fabricated on glass the transconductance g m calculated according to (1) increased from ∼31 to ∼62 µS as the W /L increased. For transistors fabricated on PEN the transconductance increased from ∼26 to ∼53 µS as the W /L increased.…”
Section: Resultsmentioning
confidence: 99%
“…The consumer uptake of wearable electronics [1] has been propelled by technology-savvy and health-aware consumers around the world. The calculator watch was the first wearable technology reported in the1980s [2].…”
Section: Introductionmentioning
confidence: 99%
“…Gameplay is not restricted to fixed locations [ 31 ] and can be done anywhere, including indoor and outdoor locations [ 22 ], since mobile exergames increasingly extract accelerometer or pedometer data from smartphones or wearable sensors [ 19 , 22 , 32 , 33 , 34 , 35 ]. These devices enable real-time activity monitoring [ 36 ] and afford immediate or frequent behavioral feedback to the user [ 37 ]. In our study, we made use of a T-shirt with an integrated accelerometer (hereafter: smart shirt) paired to a mobile exergame.…”
Section: Introductionmentioning
confidence: 99%